2022
DOI: 10.1108/ijchm-10-2021-1310
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s not a big deal’: customer misbehaviour and social washing in hospitality

Abstract: Purpose This study aims to examine customer misbehaviour in the hospitality sector during the COVID-19 pandemic. Design/methodology/approach The study draws on a cross-sectional survey of employees in the Scottish hospitality sector highlighting customer misbehaviour as a key concern during the pandemic. Prevalent types of abuse and harassment experienced are outlined along with employee and management responses to incidents of misbehaviour. Findings Verbal abuse and sexual harassment from customers are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
3
13
0
Order By: Relevance
“…Our study found that support and recognition from guests also appears to be important to hospitality employees. This finding complements and contrasts previous research on harassment, abuse and customer incivility in the hospitality sector (e.g., Booyens et al, 2022). Future research should investigate whether customer support may be particularly important in working relationships where colleague and management support are absent because the employee works alone when meeting customers (e.g., housekeeping, night shifts), or whether customer support (positive customer relationship) acts as an important resource and a buffer to requirements for (conditioned) flexibility, i.e., a protective factor that can help to prevent unhealth.…”
Section: Er 454supporting
confidence: 83%
“…Our study found that support and recognition from guests also appears to be important to hospitality employees. This finding complements and contrasts previous research on harassment, abuse and customer incivility in the hospitality sector (e.g., Booyens et al, 2022). Future research should investigate whether customer support may be particularly important in working relationships where colleague and management support are absent because the employee works alone when meeting customers (e.g., housekeeping, night shifts), or whether customer support (positive customer relationship) acts as an important resource and a buffer to requirements for (conditioned) flexibility, i.e., a protective factor that can help to prevent unhealth.…”
Section: Er 454supporting
confidence: 83%
“…At the same time, the precarious nature of hospitality employment in general and, specifically in this context, undermines the agency of workers themselves in seeking redress for abuse. The remedy, therefore, may lie with fundamental cultural changes within hospitality employment in order to give greater security and recognition of rights to the workforce (Booyens et al., 2022). For example, there is an argument that fairly rewarding workers in hospitality are less reliant on tips that has the potential to lessen customer sexual harassment (Klein et al., 2021; Kundro et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study was conducted before the pandemic started. Given that emerging research shows that customer misbehavior and abuse has worsened during and after the COVID‐19 pandemic (Booyens et al., 2022), more research is necessary to re‐examine the impact this may have had on sexual harassment within the gay tourism market and beyond. In this regard, the financial impact of the repeated lockdowns and the long‐term precarity of service work will arguably remain drivers of tolerating, accepting, and consenting to harassment as part of the job.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, anonymous online and mobile platforms (e.g. StopIT) through employee assistance programs should be offered to employees to seek psychological interventions and trauma counseling if needed, to cope with workplace incivility (Booyens et al , 2022) and to discuss their problems emanating from the workplace.…”
Section: Implications Of the Studymentioning
confidence: 99%